Beyond cold technology: A systematic review and meta-analysis on emotions in technology-based learning environments - Loderer, Kristina; Pekrun, Reinhard; Lester, James C. (Learning and instruction, 2020)
Understanding emotions in technology-based learning environments (TBLEs) has become a paramount goal across different research communities, but to date, these have operated in relative isolation. Based on control-value theory (Pekrun, 2006), we reviewed 186 studies examining emotions in TBLEs that were published between 1965 and 2018. We extracted effect sizes quantifying relations between emotions (enjoyment, curiosity/interest, anxiety, anger/frustration, confusion, boredom) and their antecedents (control-value appraisals, prior knowledge, gender, TBLE characteristics) and outcomes (engagement, learning strategies, achievement). Mean effects largely supported hypotheses (e.g., positive relations between enjoyment and appraisals, achievement, and cognitive support) and remained relatively stable across moderators. These findings imply that levels of emotions differ across TBLEs, but that their functional relations with appraisals and learning are equivalent across environments. Implications for research and designing emotionally sound TBLEs are discussed. •We reviewed 186 studies on emotions in technology-based learning.•Correlations were consistent with hypotheses derived from control-value theory.•Enjoyment correlated positively with control, cognitive support, and achievement.•Anxiety correlated negatively with these variables as well as learning strategies.•Effects were largely unaffected by moderators such as type of learning environment.